2015
DOI: 10.1002/jssc.201401330
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted emulsification microextraction coupled with high‐performance liquid chromatography for the simultaneous determination of fragrance allergens in cosmetics and water

Abstract: A simple, inexpensive, and environmentally friendly method based on ultrasound-assisted emulsification microextraction followed by solidification of floating organic drop and high-performance liquid chromatography coupled to diode array detection was developed for the simultaneous determination of 18 potentially allergenic fragrance substances. Several parameters affecting the microextraction process were investigated in detail by the "one-variable-at-a-time" approach. Optimal conditions were the following: 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…and , respectively. The applications of these methods for selected cosmetic matrices are given in Table .…”
Section: Sample Preparation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…and , respectively. The applications of these methods for selected cosmetic matrices are given in Table .…”
Section: Sample Preparation Techniquesmentioning
confidence: 99%
“…SFOD frequently used low‐toxicity solvents as extractants, such as 2‐dodecanol, 1‐undecanol and supramolecular solvents, and a small volume of solvent (30–50 μL) was large enough for an effective extraction technique . This approach was established for the isolation of parabens and allergenic fragrance substances from gel, toilette, cologne, perfume, and body milks .…”
Section: Sample Preparation Techniquesmentioning
confidence: 99%
“…Focusing on the synthesis of magnetic GR-C 8 sorbent, subsequently, the reflux time needed for the covalent attachment of octylamine on the surface of magnetic GR was studied. Elemental analysis of the resulting materials, refluxed for different time periods (6,12,24,48, 72 and 90 h) indicated that no significant differences (at 95% confidence level) among preparations were noticed with respect to the percentage of carbon loading while nitrogen diminished (See Supporting Information Table 1 ).…”
Section: Preliminary Evaluation Of the Materialsmentioning
confidence: 99%
“…To date, several studies have been developed for the extraction, separation, and determination of fragrance allergens, musks, or phthalates, at μg L −1 levels in the aquatic environment. Extraction techniques, applied so far, include SPE , SPME , stir‐bar sorptive extraction , LLE , QuEChERS , and others . The separation and determination are achieved by a variety of analytical methods including large‐volume‐injection GC–MS , thermal desorption GC–MS , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive GC x GC [19,22,24], LC-MS [20], LC-MS/MS [23], MEKC [21] are also reported. Innovative extraction methods have been developed [8,15,17,25,26] mostly for cosmetics and perfumes, but are difficult to apply to plush, plastic, wooden and other materials of toy samples. In the field of toys, traditional methods, such as ultrasonic extraction, dissolutionprecipitation and SPE, consume complex operation, plenty of time and solvents.…”
Section: Introductionmentioning
confidence: 99%